2018
DOI: 10.1158/2326-6066.cir-17-0134
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and CTLA-4 Blockade Shape the TCR Repertoire of Tumor-Infiltrating T Cells

Abstract: Immune checkpoint inhibitors activate T cells to reject tumors. Unique tumor mutations are key T-cell targets, but a comprehensive understanding of the nature of a successful antitumor T-cell response is lacking. To investigate the T-cell receptor (TCR) repertoire associated with treatment success versus failure, we used a well-characterized mouse carcinoma that is rejected by CD8 T cells in mice treated with radiotherapy (RT) and anti-CTLA-4 in combination, but not as monotherapy, and comprehensively analyzed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
133
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(142 citation statements)
references
References 45 publications
8
133
1
Order By: Relevance
“…Administration of anti‐PD1 or anti‐CTLA4 antibodies presumably helps to stabilize the PDT‐induced, highly diverse and clonally expanded, activated T cells, resulting in a more robust antitumor immunity as reported in several PDT studies listed in Table . The concept of T‐cell repertoire enrichment has been reported for radiotherapy , and as such, we propose that PDT can also play a similar role in expanding the number of activated TSA‐specific clonotypes for a more substantive and comprehensive attack on PDT‐treated tumors. Examining the T‐cell repertoire diversity status before and after PDT treatment could, therefore, be a valuable parameter to evaluate outcomes of PDT combination therapies.…”
Section: T‐cell Repertoire Enrichment By Pdt—a Forward‐looking Hypothmentioning
confidence: 80%
“…Administration of anti‐PD1 or anti‐CTLA4 antibodies presumably helps to stabilize the PDT‐induced, highly diverse and clonally expanded, activated T cells, resulting in a more robust antitumor immunity as reported in several PDT studies listed in Table . The concept of T‐cell repertoire enrichment has been reported for radiotherapy , and as such, we propose that PDT can also play a similar role in expanding the number of activated TSA‐specific clonotypes for a more substantive and comprehensive attack on PDT‐treated tumors. Examining the T‐cell repertoire diversity status before and after PDT treatment could, therefore, be a valuable parameter to evaluate outcomes of PDT combination therapies.…”
Section: T‐cell Repertoire Enrichment By Pdt—a Forward‐looking Hypothmentioning
confidence: 80%
“…Since then, a number of studies have demonstrated radiation‐dependent T‐cell priming, though often using exogenous tumour peptides such as ovalbumin (Lugade et al , ; Lee et al , ; Schaue et al , ; Sharabi et al , ). More recently, Rudqvist et al () show a radiation‐dependent increase in the number and diversity of T‐cell receptor clones. We found that splenic CD8 T cells isolated from mice bearing irradiated tumours were significantly more active towards irradiated tumour cells compared with naïve cells in vitro , suggesting increased presentation of peptides but not excluding additional effects of increased DAMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostimulatory effects arise from increased tumour peptide availability along with increased expression of MHC class I proteins on the irradiated cancer cells that allow greater access for antigen presentation (Reits et al , ; Wan et al , ; Rudqvist et al , ). Damaged tumour cells release damage‐associated molecular patterns (DAMPs) that stimulate an immune response, including enhanced recruitment and activity of antigen‐presenting cells (Schaue & McBride, ).…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies have demonstrated that radiation alters the TME to potentiate an adaptive immune response. Tumor irradiation functions as an in situ vaccine because it results in the release of tumor‐associated antigens, which activate antigen presenting cells to migrate to draining lymph nodes where they prime cytotoxic CD8+ T cells to generate an adaptive immune response, including recruitment of endogenous TILs and enhanced TCR expansion . Specifically, high dose tumor irradiation increases T cell priming due to cross‐presentation of tumor peptides via MHC class I pathway.…”
Section: Car T Cells and The Suppressive Microenvironment Of Brain Tumentioning
confidence: 99%